Explicit and implicit attitudes toward sustainability in outdoor athletes - Hoja, Sabine; Jansen, Petra (Frontiers in Psychology, 2026)
Understanding athletes' attitudes toward sustainability is essential, as sports can significantly influence environmental awareness and behavior. Differences may exist between athletes who practice individually and those who compete in teams, yet little is known about the underlying nature of these attitudes-especially when considering implicit dimensions. The present study builds on the former research by investigating whether individual and team outdoor athletes differ in both their explicit and implicit sustainable attitudes. One hundred athletes participated, with 45 from individual sports and 55 from team sports. Participants completed an explicit rating task, the Implicit Association Test, the Connectedness to Nature Scale, and a demographic questionnaire. Results indicate that individual outdoor athletes rated non-sustainable concepts as less positive than team outdoor athletes suggesting more sustainable attitudes. No differences emerged between the two groups regarding implicit attitudes and explicit attitudes toward sustainable concepts. These findings suggest that individual and team athletes may differ in their explicit evaluations of unsustainable concepts, while implicit attitudes appear more similar. This highlights the need to investigate the underlying processes in more depth.